2005
DOI: 10.1016/s0002-9440(10)62267-5
|View full text |Cite
|
Sign up to set email alerts
|

The HLA-A2 Restricted T Cell Epitope HCV Core35–44 Stabilizes HLA-E Expression and Inhibits Cytolysis Mediated by Natural Killer Cells

Abstract: Impaired activity of natural killer cells has been proposed as a mechanism contributing to viral persistence in hepatitis C virus (HCV) infection. Natural cytotoxicity is regulated by interactions of HLA-E with inhibitory CD94/NKG2A receptors on natural killer (NK) cells. Here, we studied whether HCV core encodes peptides that bind to HLA-E and inhibit natural cytotoxicity. We analyzed 30 HCV core-derived peptides. Peptide-induced stabilization of HLA-E expression was measured flow cytometrically after incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
136
2
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 46 publications
5
136
2
3
Order By: Relevance
“…In vivo HLA-E presents a mixture of peptides derived from the leader sequences of HLA class I molecules, and during infection viral peptides also may be presented (26). To rationalize our findings with previous work, we performed further degranulation assays using combinations of HCV core [35][36][37][38][39][40][41][42][43][44] and MHC class I leader peptides (27). In the presence of HCV core [35][36][37][38][39][40][41][42][43][44] , inhibition of killing mediated by 1 μM HLA-G sp was enhanced twofold ( Fig.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…In vivo HLA-E presents a mixture of peptides derived from the leader sequences of HLA class I molecules, and during infection viral peptides also may be presented (26). To rationalize our findings with previous work, we performed further degranulation assays using combinations of HCV core [35][36][37][38][39][40][41][42][43][44] and MHC class I leader peptides (27). In the presence of HCV core [35][36][37][38][39][40][41][42][43][44] , inhibition of killing mediated by 1 μM HLA-G sp was enhanced twofold ( Fig.…”
mentioning
confidence: 77%
“…These residues interact primarily with the nonsignaling CD94 moiety, which occupies the majority of the HLA-E-binding interface. CD94-NKG2A seems to be a target for viral escape, with peptides derived from CMV, HCV, HIV, and EBV binding HLA-E and subsequently inhibiting NK cells (24)(25)(26)(27). Viral peptides that inhibit at KIR also are identifiable (28), but their relevance likely is limited to the subset of individuals who have the relevant peptide-binding MHC class I allele.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first identified were conserved peptides derived from the leader sequence of various HLA class I alleles [12]; binding of these peptides enables surface expression of HLA-E molecules in most normal cells [13]. Subsequently, several HLA-Ebinding peptides have been identified that were derived from viruses, including CMV [5,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…the AD-169 UL40 [15][16][17][18][19][20][21][22][23] VMAPRTLIL peptide) is identical to a peptide common to the leader sequence of various HLA-Cw alleles [5]. Available in high amounts during CMV infection, it binds to HLA-E molecules and enables their expression at the cell surface.…”
Section: Introductionmentioning
confidence: 99%